OF NANOMATERIALS IN MODERN CONCRETE PRODUCTION PLACE (International journal of artificial intelligence, 2024)
The use of nanoparticle cements to improve their physico-mechanical properties, brand and other properties in the production of concrete and reinforced concrete products is the basis for their wide use in construction and other industries. Materials obtained on the basis of nanocements are promising building materials.